2012
DOI: 10.1159/000337218
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Short Children Born Small for Gestational Age: Effects of Growth Hormone Treatment and Postponement of Puberty

Abstract: Aims: To investigate health-related quality of life (HRQoL) in short children born small for gestational age (SGA) during growth hormone (GH) treatment and additional postponement of puberty by gonadotropin-releasing hormone analogue (GnRHa). Methods: HRQoL was studied longitudinally during 2 years of treatment in 97 short SGA children (mean age 11.6 years at start). The children were divided into three groups: prepubertal GH-treated (prep-GH) children, pubertal GH-treated (pub-GH) children, and pubertal GH-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 74 publications
2
14
0
5
Order By: Relevance
“…In concordance with our findings, previous studies showed a better QoL in GH-treated children compared to untreated children with short stature with a focus on behavioral functioning [11,14,27,28]. Lem et al [29 ]reported an increase of health-related QoL also in short children small for gestational age treated with GH. In contrast, only one study found that treatment with GH did not improve QoL in idiopathic short children [30].…”
Section: Discussionsupporting
confidence: 92%
“…In concordance with our findings, previous studies showed a better QoL in GH-treated children compared to untreated children with short stature with a focus on behavioral functioning [11,14,27,28]. Lem et al [29 ]reported an increase of health-related QoL also in short children small for gestational age treated with GH. In contrast, only one study found that treatment with GH did not improve QoL in idiopathic short children [30].…”
Section: Discussionsupporting
confidence: 92%
“…In case of a poor AH prognosis at the start of puberty, 2 yr of GnRHa in addition to GH treatment can improve AH without an adverse effect on health-related quality of life (20,43) and, as shown here, without adverse effects on BMD or body composition.…”
Section: Duration Of Treatment (Years)mentioning
confidence: 59%
“…The inclusion and exclusion criteria of the Dutch SGA study have been described before (20). Briefly, children were included when they met the following criteria: 1) birth length and/or birth weight SD score (SDS) for gestational age less than Ϫ2.0 (21); 2) chronological age of 8 yr or older; 3) prepubertal stage (Tanner stage 1) or early pubertal stage [breast stage 2-3 in girls and testicular volume Ͻ 10 ml in boys (22), with a GnRHa stimulating test indicating central puberty (23)]; 4) current height SDS less than Ϫ2.5 SDS and/or AH expectation less than Ϫ2.5 SDS (defined as a height at start of puberty Ͻ 140 cm), based on Dutch references (24); 5) well-documented growth data from birth to start of treatment; and 6) normal karyotype in all girls.…”
Section: Methodsmentioning
confidence: 99%
“…Two years of GH treatment improved HRQOL, according to both patients and parents. Improvement in HRQOL during long-term GH treatment was also observed in short children born small for gestational age [30,31]. …”
Section: Discussionmentioning
confidence: 99%